Drought monitoring with spectral indices calculated from MODIS satellite images in Hungary - Gulácsi, András; Kovács, Ferenc (JOURNAL OF LANDSCAPE ECOLOGY, 2015)
In this study a new remote sensing drought index called Difference Drought Index (DDI) was introduced. DDI was calculated from the Terra satellite's MODIS sensor surface reflectance data using visible red, near-infrared and short-wave-infrared spectral bands. To characterize the biophysical state of vegetation, vegetation and water indices were used from which drought indices can be derived. We utilized Difference Vegetation Index (DVI), Normalized Difference Vegetation Index (NDVI), Enhanced Vegetation Index (EVI), Difference Water Index (DWI), Normalized Difference Water Index (NDWI), Difference Drought Index (DDI) and Normalized Differ- ence Drought Index (NDDI) in order to perform comparative analyses. The Difference Drought Index was prov- en applicable in quantifying drought intensity. However, after comparison with reference data NDWI performed better than the other indices examined in this study. The dataset confirmed that water indices are very sensitive to changes in drought conditions. In our MODIS satellite image based research DDI and NDWI performed best, which is proven by their strong link to Pálfai Drought Index (PAI). With the conversion of spectral index values to PAI values, we are capable of determining 8-day PAI values with adequate accuracy.
Keywords: drought; remote sensing; MODIS; monitoring; spectral indices